Kurzfristige Zentralitätsschwankungen eines großstädtischen Einkaufszentrums - Ergebnisse von Kundenbefragungen in Bielefeld - Meschede, Winfried (ERDKUNDE, 1974)
From a survey carried out in Bielefeld (and neighbouring medium-sized towns) on three different days, the home addresses of 4819 shoppers were obtained. A survey of car parks secured the registration district and type of vehicle of 2492 cars. The aim of the surveys was to measure changes in the centrality of the central area of a large city and their relationship to shifts in shopper numbers and changes in their social composition. Analysis of the data produced the following major results: a) the larger number of shoppers on Saturdays than on weekdays is bound up with the greater attraction field exerted by shops in the major city on Saturday, b) the numbers of shoppers from short, medium and long distances, when reduced by a 'time threshold' factor (20-30 minute isochrone) rather than by travel costs (i. e. fred from the effects of differing population groups) are different from each of these zones when Saturdays and weekdays are compared. The greater availability of lei sure time on Saturday relativises the length of the journey and the number of shoppers from medium-to-long distan ces increases strongly as compared to a weekday. In addition, town dwellers whose higher-order needs cannot be wholly met any more in their own townacentre are extremely over-represented. In contrast, urben dwellers from the immediate vicinity, who can visit Bielefeld quite easily on a weekday avoid the overcrowded city centre on Saturday and use their own town centre. In turn, these centres are not competitive for geople from the surrounding rural areas when their total travel time is calculated. Their additional time penalty in visiting the big city is not great. c) larger numbers of shoppers and a higher proportion of urban dwellers from medium-to-long distances are linked with a higher proportion of financially weaker central area visitors (owners of small cars).